Cardiac α-Actin (ACTC1) Gene Mutation Causes Atrial-Septal Defects Associated With Late-Onset Dilated Cardiomyopathy. (August 2019) - Frank, Derk; Yusuf Rangrez, Ashraf; Friedrich, Corinna; Dittmann, Sven; Stallmeyer, Birgit; Yadav, Pankaj; Bernt, Alexander; Schulze-Bahr, Ellen; Borlepawar, Ankush; Zimmermann, Wolfram-Hubertus; Peischard, Stefan; Seebohm, Guiscard; et al.
Abstract : Background: Familial atrial septal defect (ASD) has previously been attributed primarily to mutations in cardiac transcription factors. Here, we report a large, multi-generational family (78 members) with ASD combined with a late-onset dilated cardiomyopathy and further characterize the consequences of mutant α-actin. Methods: We combined a genome-wide linkage analysis with cell biology, microscopy, and molecular biology tools to characterize a novel ACTC1 (cardiac α-actin) mutation identified in association with ASD and late-onset dilated cardiomyopathy in a large, multi-generational family. Results: Using a genome-wide linkage analysis, the ASD disease locus was mapped to chromosome 15q14 harboring the ACTC1 gene. In 15 affected family members, a heterozygous, nonsynonymous, and fully penetrant mutation (p. Gly247Asp) was identified in exon 5 of ACTC1 that was absent in all healthy family members (n=63). In silico tools predicted deleterious consequences of this variant that was found absent in control databases. Ultrastructural analysis of myocardial tissue of one of the mutation carriers showed sarcomeric disarray, myofibrillar degeneration, and increased apoptosis, while cardiac proteomics revealed a significant increase in extracellular matrix proteins. Consistently, structural defects and increased apoptosis were also observed in neonatal rat ventricular cardiomyocytes overexpressing the mutant, but not native human ACTC1. Molecular dynamics studies and additional mechanistic analyses in cardiomyocytes confirmed actin polymerization/turnover defects, thereby affecting contractility. Conclusions: A combined phenotype of ASD and late-onset heart failure was caused by a heterozygous, nonsynonymous ACTC1 mutation. Mechanistically, we found a shared molecular mechanism of defective actin signaling and polymerization in both cardiac development and contractile function. Detection of ACTC1 mutations in patients with ASD may thus have further clinical implications with regard to monitoring for (late-onset) dilated cardiomyopathy. Abstract : Supplemental Digital Content is available in the text.